Influence of the operation of endotrabecuoloectomy on glaucoma optical neuropathy course (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Compensation of IOP does not always lead to a stabilization of the glaucomatous process. Therefore, functional and morphometric studies to evaluate the effectiveness of glaucoma surgery are important and necessary. Purpose. To evaluate hypotensive effect of endotrabeculoectomy and influence of the operation on stabilization of glaucoma progressing. Material and methods. The investigation was done in two groups. The first group (22 patients, 23 eyes) was with open-angle glaucoma who underwent endotrabeculoectomy, and the second group (95 patients, 107 eyes) had open-angle glaucoma and cataract who underwent combined phacoemulsification and endotrabeculoectomy. Results. In the first group tonometric IOP decreased by 7.8+0.7 mm Hg and was 18.6+1.1 (p
Keywords: Endotrabecuoloectomy; intraocular pressure; field of vision; OCT; thickness of the retinal nerve fiber layer